FIELD TRIP AND REVOLUTIONIZING THE WAY OF THINKING THE STUDENT OF TOURISM STUDY PROGRAMME OF UNIVERSITAS NEGERI PADANG - Dwi Pratiwi Wulandari; Pretty Shinta Siboro; Hariyadi Hariyadi (Ensiklopedia of Journal, 2026)
This study aims to analyze the influence of the field trip method on the critical thinking skills of undergraduate students in the Tourism Study Program at Universitas Negeri Padang. The research employed a descriptive quantitative approach using simple linear regression analysis. The sample was selected purposively from students who had participated in field trip-based learning activities. The linearity test produced a significance value of 0.385 ( 0.05), indicating a linear relationship between the field trip variable (X) and critical thinking skills (Y). The regression analysis showed that the model was statistically significant, with an F-value of 103.989 and a significance level of 0.000 ( 0.05), meaning the regression model is suitable for predicting the dependent variable. The t-test resulted in a t-value of 3.825 with a significance level of 0.000, indicating that the field trip variable has a significant effect on students’ critical thinking. The regression coefficient was 0.815 with a significance level of 0.000, which means that an increase of 1 unit in the field trip variable will result in a 0.815-unit increase in critical thinking skills. These findings confirm that the field trip method has a positive and significant influence and is an effective learning strategy for enhancing the critical thinking abilities of tourism students.Keywords: Learning Methode, Fielf Trip, Critical Thinking Skills